ENTT/ENTTR: A Family of Improved Emerging NVM-Based Trojan Triggers and Resets - Nagarajan, Karthikeyan; Khan, Mohammad Nasim Imtiaz; Ghosh, Swaroop (Frontiers in Nanotechnology, 2022)
Hardware Trojans in Integrated Circuits (ICs), that are inserted as hostile modifications in the design phase and/or the fabrication phase, are a security threat since the semiconductor manufacturing process is increasingly becoming globalized. These Trojans are devised to stay hidden during standard structural and functional testing procedures and only activate under pre-determined rare conditions (e.g., after a large number of clock cycles or the assertion of an improbable net). Once triggered, they can deliver malicious payloads (e.g., denial-of-service and information leakage attacks). Current literature identifies a collection of logic Trojans (both trigger circuits and payloads), but minimal research exists on memory Trojans despite their high feasibility. Emerging Non-Volatile Memories (NVMs), such as Resistive RAM (RRAM), have special properties such as non-volatility and gradual drift in bitcell resistance under a pulsing voltage input that make them prime targets to deploy hardware Trojans. In this paper, we present two delay-based and two voltage-based Trojan triggers using emerging NVM (ENTT) by utilizing RRAM's resistance drift under a pulsing voltage input. Simulations show that ENTTs can be triggered by reading/writing to a specific memory address N times (N could be 2500-3500 or a different value for each ENTT design). Since the RRAM is non-volatile, address accesses can be intermittent and therefore stay undetected from system-level techniques that can identify continuous hammering as a possible security threat. We also present three reset techniques to de-activate the triggers. The resulting static/dynamic power overhead and maximum area overhead incurred by the proposed ENTTs are 104.24uW/0.426$uW and 9.15um2, respectively in PTM 65nm technology. ENTTs are effective against contemporary Trojan detection techniques and system level protocols. We also propose countermeasures to detect ENTT during the test phase and/or prevent fault-injection attacks during deployment.